Sistem Informasi Dealer Sepeda Motor Bekas Di Kecamatan Bangkinang Kota ( Programming) - Fezi Alfarisy, Muhammad; Musridho, Raja Joko; Adeswastoto, Hanantatur (Journal on Pustaka Cendekia Informatika, 2023)
Motorcycles are the most dominant means of transportation today, especially for the people of Bangkinang, and some people even prefer to look for used motorbikes because the prices are more affordable. Before someone starts deciding to get the desired means of transportation, they usually start by making several considerations. To find a used motorbike with certain criteria is a job that is quite difficult and troublesome and takes a long time, in order to get a used motorbike that really meets expectations, someone is willing to search every shop, this of course requires quite a lot of time and money. Therefore, this thesis builds a Web- based Information System for Used Motorcycle Dealers in Bangkinang Kota District so that it can help people find information on selling used motorbikes according to their needs. In testing the system using the blackbox testing method, all the features in this system run 100% indicating that the system is free of bugs.